PERDAGANGAN PEREMPUAN PERSPEKTIF YURIDIS - Siti Rochmiyatun (An Nisa'a, 2012)
The criminal action of woman/girl trade as one of the forms of violence against women is a kind of humanity crime. This criminal action has been listed in the Article 297 of the Criminal Code, but this crime keeps on occurring and becomes a more complex form or objective of women trade. The cases of woman/girl trade in Palembang City  reported to the Police Department of the Provincial Government of South Sumatera from 2003 to January 2004 amount to 8 (eight) cases, six of which have been sentenced by Pengadilan Negeri (The Court of First Instance) IA Class of Palembang. One case did not have a sufficient proof and one case was not clear. The form or the objective of woman/girl trade inPalembangCity is to make the victims the prostitutes including domestic and international woman/girl trade. This writing describes more comprehensively how woman/girl trade inPalembang is.